Pengaturan Pertanggungjawaban Mutlak Wajib Pajak Di Indonesia Dalam Perspektif Keadilan Dan Kemanfaatan Umum - Sinaga, Henry Dianto Pardamean (Jurnal Hukum & Pembangunan, 2019)
The increasing of tax evasion and tax avoidance, due to lack of taxpayer’s liability regulation in tax legislation, has been very detrimental to state revenues. Based on normative juridical research with descriptive-comparative-prescriptive approach which has been done, it is concluded that the regulation of strict liability of taxpayers of Indonesia can: 1) fulfill the sense of justice in terms of equality and or fairness as long as it meets the condition that reflects of material justice and formal justice which must be regulated explicitly in tax legislation; and 2) provide public benefit to the state in handling the social welfare and regulation offences and or in handling the rise of abnormally dangerous behaviors that require a due care standard in the taxpayer’s business environment. It is recommended to be explicitly set about the criteria of strict liability and widening the defenition of any person, including individual and corporation, in tax legislation.